The Comparative Study of Gompertz Exponential Distribution and other three Parameter Distributions of Exponential Class - Johnson Ademola, Adewara; John Sunday, Adeyeye (Covenant Journal of Physical and Life Sciences, 2021)
Statistical distributions are very useful in describing and predicting real world phenomena. In this paper, a new continuous model called Gompertz exponential distribution is defined and studied. Its resulting densities and statistical properties were carefully derived and the method of maximum likelihood was proposed in estimating the model parameters. A simulation on R was done to assess the performance of the parameters of the new model. Gompertz exponential distribution was illustrated with an application to real-life data. The result shows that Gompertz exponential distribution performs better than other three-parameter distributions such as Kumaraswamy–exponential distribution, Generalized Gompertz distribution, and Three-Parameter Lindley distribution.